ANALISIS PENDAPATAN USAHATANI PADI SAWAH BERDASARKAN SISTEM BAGI HASIL DI DESA WOLAANG KECAMATAN LANGOWAN TIMUR KABUPATEN MINAHASA - Anatasya Angelina Lelet; Yolanda Pinky Ivanna Rori; Joachim Noch Karel Dumais (AGRI-SOSIOEKONOMI, 2019)
The objective of this research is to analyze the income of rice farming based on the revenue sharing system in Wolaang Village, East Langowan sub-district, Minahasa Regency. This research was conducted for 3 month, starting from January to March 2019. The Samples of farmers is using simple random sampling method (simple random). Data collected in this study are primary data and secondary data. Primary data was obtained from direct interviews with 30 farmer. While secondary data obtained from BP3K East Langowan sub-district and BPS Minahasa Regency, books available at local bookstores and the internet such as google searching to access articles from various scientific journals and thesis from other universities related to the topic of this research, especially income analyze. The results showed that the income received by landowners was Rp.13,462,500 while the income received by smallholders was smaller than that of landowners, namely Rp.9,940,865.*jnkd+eprm*